Effect of Aspergillus niger prolyl endopeptidase in patients with celiac disease on a long-term gluten-free diet - Stefanolo, Juan Pablo (2024)
Background/Aim: The gluten-free diet has limitations, and there is intense research in the development of adjuvant therapies. Our aim was to examine the effects of orally administered Aspergillus niger endopeptidase (AN-PEP) on inadvertent gluten exposure and symptom prevention in adult patients with celiac disease (CeD) following their usual gluten-free diet (GFD).Methods: This was an exploratory, double-blind, randomized, placebo-controlled trial that enrolled patients with CeD on a long-term GFD. After a four-week run-in period, patients were randomized to 4 weeks of 2 AN-PEP capsules (GliadinX. AVI Research LLC; USA) at each of 3 meals/day or placebo. Outcome endpoints were: 1- the average weekly stool gluten immunogenic peptides (GIP) between the run-in and end of treatments, and between AN-PEP and placebo; 2) the Celiac Symptom Index (CSI); 3- CeD-specific serology; and 4- the quality of life. Stool samples were collected for GIP by ELISA every Tuesday and Friday during run-ins and treatments.Results: 40 patients were randomized to the intention-to-treat analysis, and three were excluded from the per-protocol assessment. Overall, 628/640 (98.1%) stool samples were collected. GIP was undetectable (<0.08 µg/g) in 65.6% of samples, and no differences between arms were detected. Only 0.5% of samples had GIP concentrations sufficiently high (>0.32µg/g) to potentially cause mucosal damage. Median GIP concentration in the AN-PEP arm was 44.7% lower than in the run-in period. One-third of patients exhibiting GIP >0.08 µg/g during run-in had lower or undetectable GIP after AN-PEP treatment. Compared with the run-in period, the proportion of symptomatic patients (CSI >38) in the AN-PEP arm was significantly lower (p<0.03). AN-PEP did not result in changes in specific serologies.Conclusions: This exploratory study, conducted in a real-life setting, revealed high adherence to the GFD. The AN-PEP treatment did not significantly reduce overall GIP stool concentration. However, given the observation of a significantly lower prevalence of severe symptoms in the AN-PEP arm in patients following their usual GFD, further clinical research is warranted.